2021
DOI: 10.3892/mi.2021.5
|View full text |Cite
|
Sign up to set email alerts
|

Application of marine collagen for stem‑cell‑based therapy and tissue regeneration (Review)

Abstract: tissue engineering and regenerative medicine is becoming an important component in modern biological scientific research. tissue engineering, a branch of regenerative medicine, is a field that is actively developing to meet the challenges presented in biomedical applications. this particularly applies to the research area of stem cells and biomaterials, due to both being pivotal determinants for the successful restoration or regeneration of damaged tissues and organs. Recently, the development of innovative ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…There is still limited literature regarding MGO’s role in the calcification of bone cells, yet research has reported that MGO generates mitochondrial dysfunction in liver cells . It has been reported that certain collagen amino acids, such as glycine, alanine, glutamine, and asparagine, can selectively induce osteogenesis by activating the focal adhesion kinase/JNK signaling cascade and runt-related transcription factors in bone marrow-derived MSCs . Rena et al proved that the enhanced rates of fibril production by tilapia-scale COLL may promote early osteogenic induction via upregulating alp , opn , and bmp-2.…”
Section: Discussionmentioning
confidence: 99%
“…There is still limited literature regarding MGO’s role in the calcification of bone cells, yet research has reported that MGO generates mitochondrial dysfunction in liver cells . It has been reported that certain collagen amino acids, such as glycine, alanine, glutamine, and asparagine, can selectively induce osteogenesis by activating the focal adhesion kinase/JNK signaling cascade and runt-related transcription factors in bone marrow-derived MSCs . Rena et al proved that the enhanced rates of fibril production by tilapia-scale COLL may promote early osteogenic induction via upregulating alp , opn , and bmp-2.…”
Section: Discussionmentioning
confidence: 99%
“…Freeze-dried collagen was dissolved in acetic acid (0.1 mol L −1 ) by the way of continuous stirring for 5 h at room temperature (RT). Collagen stock solution was prepared by adding chloroform to the mixture in proportion 1:9, the resulting solution was stored overnight at +4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Collagen ranks as one of the most widely studied naturally occurring polymers and as a major component of the extracellular matrix of connective tissues such as bones, cartilage, ligaments and skin. 1 As the most ubiquitous protein in the mammalian body, collagen plays a key role in the formation of organs and tissues and is considered to be an appropriate scaffold for maintaining cell culture proliferation. Other aspects of cell behavior affected by collagen are cell adhesion, differentiation, proliferation, and cellular migration, so it makes it an ideal material for cell culture research.…”
Section: Introductionmentioning
confidence: 99%
“…These marine polymers are multifunctional, with a range of therapeutic uses, from anti-inflammatory to antiviral purposes [ 31 ]. Among many natural polymers, including chitin and alginates, collagen is one of the most extensively studied and applied polymers in clinical settings, because of its properties [ 32 ]. It plays a fundamental role in the formation of tissues and organs and it is involved in various functional and structural aspects of cells.…”
Section: Sources Of Marine Bioactive Compoundsmentioning
confidence: 99%